Money-Based Versus Exchange-Rate-Based Stabilization : Is There Space for Political Opportunism? - Aisen, Ari (IMF Working Papers; Working Paper, 2004)
In response to high and chronic inflation, countries have adopted different stabilization policies. However, the extent to which these stabilization programs were designed for political motives is not clear. Since exchange-rate-based stabilizations (ERBS) create an initial consumption boom followed by a contraction, whereas money-based stabilizations (MBS) generate a consumption bust followed by a recovery, policymakers may consider the timing of elections when determining the nominal anchor for stabilization. This paper finds strong evidence that the choice of nominal anchor depends on elections, implying the existence of political opportunism. ERBS are, on average, launched before elections while MBS are set after them.